Regional gray matter volume increases following 7days of voluntary wheel running exercise: A longitudinal VBM study in rats - Sumiyoshi, Akira; Taki, Yasuyuki; Nonaka, Hiroi; Takeuchi, Hikaru; Kawashima, Ryuta (NeuroImage (Orlando, Fla.), 2014)
The effects of physical exercise on brain morphology in rodents have been well documented in histological studies. However, to further understand when and where morphological changes occur in the whole brain, a noninvasive neuroimaging method allowing an unbiased, comprehensive, and longitudinal investigation of brain morphology should be used. In this study, we investigated the effects of 7days of voluntary wheel running exercise on regional gray matter volume (rGMV) using longitudinal voxel-based morphometry (VBM) in rats. Eighteen pairs of adult male naïve Wistar rats were randomized to the exercise or control condition (one rat for each condition from each pair). Each rat was scanned in a 7.0-T MRI scanner at three time points: before exercise, after 7days of exercise, and after 7days of follow-up. The T2-weighted MRI images were segmented using the rat brain tissue priors that were recently published by our laboratory, and the intra- and inter-subject template creation steps were followed. Longitudinal VBM analysis revealed significant increases in rGMV in the motor, somatosensory, association, and visual cortices in the exercise group. Among these brain regions, rGMV changes in the motor cortex were positively correlated with the total distance that was run during the 7days of exercise. In addition, the effects of 7days of exercise on rGMV persisted after 7days of follow-up. These results support the utility of a longitudinal VBM study in rats and provide new insights into experience-dependent structural brain plasticity in naïve adult animals. •A longitudinal voxel-based morphometry (VBM) study in rats was employed.•Seven days of wheel running increased the regional gray matter volume.•The changes in the cerebral cortex persisted after 7days of follow-up.•The changes in the motor cortex correlated with the total distance that was run.•These results support the utility of a longitudinal VBM study in rats.